Pinky swear : a novel - Girard, Danielle, 1970- (Emily Bestler Books/Atria, 2026)
"Once, Lexi thought she knew everything about Mara Vannatta. Best friends since middle school, they drifted apart after a tragedy derailed their senior year. But when Mara shows up on Lexi's doorstep sixteen years later fleeing an abusive husband, Lexi takes her in without question. Lexi's own marriage has been strained by her desire to have a baby, and when Mara offers to become her surrogate, their friendship feels stronger than ever. But four days before the due date, Mara disappears. Lexi is shocked but certain there must be something wrong--Mara would never willingly leave with her unborn child. Or would she? As she embarks on a perilous cross-country hunt for the truth, Lexi is forced to reconsider a friendship she thought she knew--and what really happened that terrible night their senior year. How many secrets lie in their shared past, waiting to be uncovered? And just how far will Lexi go to bring her child safely home?"--